Exploring the technological drivers of economic growth and development: Insights from a firm-level survey in Eastern Cape Province, South Africa - Effiong, Mfonobong Okokon; Panicker, Manoj (International Journal of Innovative Research and Scientific Studies, 2025)
This study assessed the contribution of technology to South Africa's economic growth and development. The results of the Principal Component Analysis (PCA) extracted six components explaining 100% of the variance in the data, with technological advancement and innovation (Component 1, 27.87% variance), business environment, and demographic factors (Component 2, 19.71% variance), and human capital and social development (Component 3, 16.17% variance) emerging as significant factors. The Tobit regression analysis revealed that inadequate training (-0.2971, p=0.002) and access to skilled ICT staff (-0.1786, p=0.045) negatively and significantly affected new technology adoption at 5% levels. Gender diversity promotes economic development, although not significantly (0.2625, p=0.130) while E-commerce usage had an insignificant effect on new technology adoption (-0.0678, p=0.216). For robustness, the Confirmatory Factor Analysis (CFA) validated the factor structure, and Structural Equation Modeling (SEM) analysis confirmed the relationships between factors and economic growth. The results showed that technological advancement (0.45, p=0.000), business environment (0.31, p=0.004), and human capital (0.39, p=0.002) significantly drive economic growth. The study's findings align with existing literature and provide valuable insights for policymakers and stakeholders to prioritize investments in technological advancement and innovation, particularly in areas such as digital infrastructure and skills development to foster economic growth and development in South Africa.